1996
DOI: 10.1161/01.str.27.5.875
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic Therapy of Acute Basilar Artery Occlusion

Abstract: Recanalization of acute BA occlusion reduces mortality significantly. Length of BA obstruction and state of the collaterals are additional independent variables affecting survival. Young patients with monosegmental embolic occlusion of the BA seem to have the best chance to considerably profit from thrombolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
158
1
6

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(177 citation statements)
references
References 31 publications
11
158
1
6
Order By: Relevance
“…2,8,9 Recanalization rates ranged from 40% to 100%, on average Ϸ50% to 60% in line with the results from the Prolyse in Acute Cerebral Thromboembolism II (PROACT II) trial. 10 Survival in patients without recanalization ranged from 0% to 20% as opposed to 40% to 80% in those with recanalization.…”
Section: B Asilar Artery Thrombosis (Bat) Is a Rare But Mostsupporting
confidence: 66%
See 1 more Smart Citation
“…2,8,9 Recanalization rates ranged from 40% to 100%, on average Ϸ50% to 60% in line with the results from the Prolyse in Acute Cerebral Thromboembolism II (PROACT II) trial. 10 Survival in patients without recanalization ranged from 0% to 20% as opposed to 40% to 80% in those with recanalization.…”
Section: B Asilar Artery Thrombosis (Bat) Is a Rare But Mostsupporting
confidence: 66%
“…6,7 Most studies suffered from small numbers: Ͻ10 patients with only a few in the range of 40 to 50 patients. 2,8,9 All had an open, retrospective or partly prospective design with differing treatment regimens, mostly IA thrombolytic drugs formally rendering level III evidence at best.…”
Section: B Asilar Artery Thrombosis (Bat) Is a Rare But Mostmentioning
confidence: 99%
“…[13][14][15][16][17][18] The largest adult series, the Basilar Artery International Cooperation Study (BASICS), reported 619 patients with BAO of whom over half (328 of 619) received intra-arterial tPA and other mechanical endovascular treatments. Overall mortality was 39%, and 31% survived with an mRankin scale score of 4 or 5 for a 70% frequency of 'poor outcome' by the authors' definition.…”
Section: Discussionmentioning
confidence: 99%
“…A nonrandomized trial compared patients with and without hyperdensity of the MCA territory at baseline CT who were then given intravenous or intra-arterial rt-PA. Intravenous rt-PA therapy was associated with less favorable outcomes in patients with hyperdense MCA sign as compared to patients without it 33 . Although observational studies of urokinase and rt-PA for intra-arterial treatment of basilar artery occlusion have shown encouraging results, there are no randomized clinical trials with adequate statistical power [34][35][36] . A systematic review found no significant differences between intravenous or intra-arterial thrombolysis for basilar artery occlusion 37 .…”
Section: Protocol For Intra-arterial Thrombolysismentioning
confidence: 99%